Association between sleep duration, sleep quality and hyperlipidemia in middle-aged and older Chinese: The Dongfeng–Tongji Cohort Study. (29th August 2020) - Wang, Dongming; Chen, Jianghao; Zhou, Yun; Ma, Jixuan; Zhou, Min; Xiao, Lili; He, Meian; Zhang, Xiaomin; Guo, Huan; Yuan, Jing; Chen, Weihong
Abstract: Aims: This study aimed to evaluate the relationship between sleep duration, sleep quality and hyperlipidemia in middle-aged and older Chinese. Methods: We included 20, 712 individuals at baseline from September 2008 to June 2010, and they were followed-up until October 2013. Hyperlipidemia was defined according to the Chinese guidelines on the prevention and treatment of dyslipidemia in adults. Sleep duration was self-reported and sleep quality was evaluated with a questionnaire that was designed according to the Pittsburgh Sleep Quality Index. Logistic regression and Cox proportional hazard models were conducted to explore the associations. Results: In the cross-sectional analyses, longer sleep duration (≥10 h) was significantly associated with higher prevalence of hyperlipidemia (odds ratio (OR) = 1.17, 95% confidence interval (CI) = 1.02–1.35) after adjusting for potential confounders. The ORs of hyperlipidemia were significantly elevated among participants with impaired sleep quality (OR = 1.14, 95% CI = 1.08–1.22) and poor sleep quality (OR = 1.20, 95% CI = 1.08–1.34) when compared to those with good sleep quality. In the longitudinal analyses, compared to participants with a sleep duration of 7–<8 h, those with a sleep duration of 9–<10 h (hazard ratio (HR) = 1.19, 95% CI = 1.04–1.35) and ≥10 h (HR = 1.27, 95% CI = 1.02–1.58) showed significantly higher risk of hyperlipidemia after adjusting for potential confounders. However, no statistically significant association was found between impaired or poor sleep quality and hyperlipidemia. Conclusions: Longer sleep duration was significantly associated with higher risk of hyperlipidemia. Impaired or poor sleep quality were associated with elevated prevalence of hyperlipidemia, but not with the incidence of hyperlipidemia.